Role Of Integrated Crop Management Field Schools In Increasing Rice Production Results - Lina Asnamawati; Timbul Rasoki; Is Eka Herawati (UNIVED Press, Dehasen University Bengkulu, 2023)
Field School - Integrated Crop Management (SL-PTT) is a form of school where the entire teaching and learning process is carried out in the field, which is carried out on the land of PTT participating farmers in an effort to increase national rice production. This SL-PTT guide is the result of discussions with the Directorate General of Food Crops and the Agricultural HR Development Agency. So it is very interesting to examine (a) the role of integrated crop management field schools in increasing rice production. Respondents for this study were selected purposively, namely 1 extension worker and 4 heads of farmer groups. The research results show 1. The influence of adult education methods (andragogy) on farmers in SLPTT activities, namely the learning process in SL-PTT starts with activities which then provide personal experiences, express these experiences, analyze problems that occur, and conclude the results of activities. Every learner is encouraged to be able to observe reality, express experiences and ideas, analyze facts, make decisions, and carry out activities together. The role of SLPTT is to increase knowledge and skills in recognizing potential, preparing farming plans, overcoming problems, making decisions, and applying technology that is appropriate to local resource conditions in a synergistic and environmentally sound manner, so that farming becomes efficient, highly productive and sustainable.ACT Keywords: Role, Integrated Crop Management Field School, Rice Production Results